(untitled) (Hematology Meeting Reports, 2009)
Despite the advent of numerous new chemotherapeutic agents over the last 25 years, only limited progress in the treatment of non-Hodgkin’s lymphoma (NHL) has been made with these agents alone. In recent years, several new antibody-based treatments have demonstrated promising results in NHL suggesting tangible improvements in relapse free and overall survival. These new treatment approaches have included radioimmunotherapy (RIT) with 90Y-labeled ibritumomab tiuxetan and 131I-labeled tositumomab. RIT utilizes continuous delivery of low-dose radiation via radioactive isotopes conjugated to monoclonal antibodies that target the CD20 antigen located on most (>90%) B-cell lymphomas. Clinical trials of 90Y-ibritumomab tiuxetan and 131I-tositumomab have indicated that these agents are effective and well tolerated for adult patients with relapsed or refractory CD20+ follicular B-cell NHL, with the ability to produce superior overall and complete response rates to those achieved with existing therapies. A high proportion of patients who achieve a complete response with 90Y-ibritumomab tiuxetan or 131I-tositumomab exhibit durable remissions of several years - despite the presence of risk factors for poor response or early relapse. In addition, failure to respond to previous anti-lymphoma therapy, including rituximab, does not appear to preclude achieving a long-term response with 90Y-ibritumomab tiuxetan. RIT with 90Y-ibritumomab tiuxetan or 131I-tositumomab has also been shown to be effective in patients with follicular NHL when used as first-line therapy or following first-line, short-course chemotherapy ± rituximab regimens, but further clinical studies are needed to determine the long-term efficacy of these approaches.